Cultivating a Flourishing Intellectual Landscape for a Human-Centered and Sustainable Future: Sparking the Fusion of Society 5.0 and Collective Intelligence (Hybrid) Ecosystem Frameworks - Tornjanski, Vesna; Khan, Munir Hayet; Adamopoulos, Ioannis; Vuk, Mirčetić; Mihić, Marko; Aslan, Imran; Daoud, Mohammad; Karabašević, Darjan; Abdelwaheb, Sakhri (INTI International University, 2026)
This study advances a novel conceptual framework for reimagining global knowledge systems through the integration of the visionary principles of Society 5.0 and the evolving potential of a Collective Intelligence (Hybrid) Ecosystem. It seeks to resolve the limitations of fragmented and static models by proposing a dynamic, resilient, and human-centered approach that aligns technological advancement with social equity, sustainability, and holistic well-being. A secondary research method is employed, grounded in a systematic literature review and supported by a mixed-method design. The structural framework incorporates key elements of the Beckhard and Harris change model, while a PRISMA-guided Systematic Literature Review (SLR), integrated with a Five-Stage Analytical Model, enables rigorous analysis, synthesis, and redevelopment of existing knowledge systems. The findings reveal a global landscape shaped by eleven critical and widely recognized challenges that require renovated and cohesive strategies and solutions. These insights align with both the SDGs and the emerging HSDGs, proposing an integrative and actionable framework. Table 1 presents these strategies and solutions in a holistic manner, emphasizing the reclamation of agency, the promotion of multidisciplinary collaboration, and the cultivation of a society designed for comprehensive well-being. This analysis pioneers a groundbreaking conceptual synthesis and introduces a human-centered, responsive, and forward-compatible intellectual infrastructure, thought paramount for steering the challenges of the 21st century. Through this original integration, the study redefines how knowledge mechanisms are envisioned, structured, and carried out. This research contributes to both theory and practice through the design of an actionable and scalable pattern for policymakers, scholars, and global stakeholders, supporting the healthy evolution toward more inclusive, adaptive, and sustainable knowledge ecosystems.